Into The Grey: The Lived Experience Of Clinical Instructors Turned Frontliners In The Now Normal - Evangelista, Portia A.; Bautista, Susana C. (Technium Social Sciences Journal, 2023)
Abstract- Frontline health workers are the backbone of effective health systems – they are often based in the community and come from the community they serve, they play a critical role in providing a local context for proven health solutions, and they connect families and communities to the health system. Supartini (2022) resolute that nurses can create a more comfortable and comforting environment for the patients they serve especially in times of uncertainty. Undesirably, as the Philippines scuffled with the effect of the COVID-19 pandemic, the Department of Health is filling up the slots for much-needed healthcare workers in both the private and public sectors to help the country battle the COVID19 pandemic (Department of Health, 2020). Likewise, Tomacruz (2021) mentioned the government is also facing another battle that health workers groups warned mass resignations and protests could take place in hospitals across the country if the government does not fulfill its promise to improve support for the sector. Hence, American Nurses Association (2020) denounced nurses may struggle with the call and may choose not to respond. Consequently, nurses account for the biggest chunk of hires by profession. This study aimed at understanding and unveiling into the grey: the lived experiences of clinical instructors turned frontliners in the now normal. The researcher utilized the phenomenological research design to understand and explore the lived experiences of clinical instructors as frontliners in the now normal. The substantial outcomes of the study as to the lived experiences of clinical instructors turned frontliners in the now normal: ten (10) themes shared reality pertained to the lived experiences of clinical instructors turned frontliners in the now normal. It was disclosed that achieving professional goals, financial support and self-development, fulfilling job, shaping the lives of young people vs. providing hands on care for patients, intense physical and emotional pressure, work commitment and dedication, competitive pay was livened and appreciated by the clinical instructors who left the academe and served as frontliners in now normal. Moreover, coping mechanisms with demands and challenges of respondents involved prioritizing, time management, benefits, adaptability and self-care